A hidden cost of convenience: Disparate impacts of a program to reduce burden on probation officers and participants - Saunders, Jessica (Criminology & public policy, 2021)
Research Criminal justice practitioners increasingly seek out efficient means of community supervision supplanting face-to-face interactions with practices that are less onerous to administrators and clients. We examined the differential impact of remote supervision for low-risk probationers by race. Remote reporting greatly reduces or eliminates in-person meetings where race would be salient; however, it also creates conditions where an officer may rely more heavily on heuristics. We found the program drastically reduced violations, but also exacerbated the racial discrepancy in reporting high discretion violations. Policy Implication The study illustrates how integrating an empirical test of racial discrepancies into program evaluation can illuminate conditions that amplify implicit bias. Our findings illustrate how a program with unequivocally positive outcomes for low-risk probationers overall can further amplify racial disparities, particularly when the probation officer has more discretion. By creating a statistically equivalent group of clients who receive probation-as-usual, our evaluation strategy measures this bias by comparing consequences for which an agent has high discretion against those for which they have low or no discretion for program participants. This approach is replicable across many criminal justice practices.